MCM-41 as support for immobilization of NAR-1 bacterial consortium in the biodegradation of remazol black B [electronic resource] - Kogulabalan Ilan Sollan, 1985- (2013)
Thesis (Sarjana Sains (Biosains)) - Universiti Teknologi Malaysia, 2013